Synergistic optimization of microstructures and properties of electrodeposited Ni–CeO2 composite coatings with CeO2 microparticles and CeO2 nanoparticles - Shuxin You; Shilong Xing; Chuanhai Jiang (Journal of Materials Research and Technology, 2024)
The synergistic mechanism of microparticles and nanoparticles on optimizing microstructures homogeneity and enhancing microhardness and corrosion resistance of mixed coatings was deeply researched by co-electrodepositing CeO2 microparticles and CeO2 nanoparticles into nickel matrix. Microparticles contribute to enhancing the microhardness of the coating, while nanoparticles promote the homogeneity of the microstructure, thereby improving the corrosion resistance of the coating. Therefore, by co-electrodepositing microparticles and nanoparticles into the nickel matrix, microparticles and nanoparticles in the nickel matrix generate a synergistic optimization effect, combining the advantages of microparticles and nanoparticles. Microparticles are mainly responsible for enhancing the microhardness of the coating, while nanoparticles are responsible for promoting the homogeneity of the microstructure in the coating, maintaining a homogeneous distribution of microhardness, and improving the corrosion resistance of the coating. Ultimately, the mixed coating achieves both high microhardness and excellent corrosion resistance, along with homogeneous microhardness distribution.